2016
DOI: 10.1159/000443177
|View full text |Cite
|
Sign up to set email alerts
|

Equol Effectively Inhibits Toxic Activity of Human Neutrophils without Influencing Their Viability

Abstract: Equol (7,4′-dihydroxy-isoflavan, or 4′,7-isoflavandiol) is a chroman derivative produced by intestinal bacteria in response to soy isoflavone intake in some, but not in all, humans. Equol shows strong anti-oxidant, anti-estrogenic, anti-cancerous and anti-inflammatory properties. The antioxidative capacity of equol has recently received considerable attention, and it has been used for preventing and treating several diseases. We investigated the effect of equol on human neutrophils, extra- and intracellular fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…However, we think that the high concentration of equol may potentially inhibit NET formation. Pažoureková et al (31) reported that a high concentration of equol suppressed ROS production in neutrophils. The inhibition of ROS production leads to PAD4 nuclear transfer inhibition, which may decrease NET formation.…”
Section: Discussionmentioning
confidence: 99%
“…However, we think that the high concentration of equol may potentially inhibit NET formation. Pažoureková et al (31) reported that a high concentration of equol suppressed ROS production in neutrophils. The inhibition of ROS production leads to PAD4 nuclear transfer inhibition, which may decrease NET formation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this genus is currently formed by one species, A . equolifaciens , which produces an isoflavone metabolite, named equol, with anti-cancerous and anti-inflammatory properties 37 , 38 . Moreover, studies reveal that equol is exclusively produced by the intestinal microbiota 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The equol protected macrophages from oxidative stress induced by L-lactate dehydrogenase or oxLDL by reducing the lipid peroxidation product malondialdehyde (MDA), enhancing the antioxidant glutathione, or increasing the activities of the antioxidant enzyme superoxide dismutase (SOD) [89,90]. Equol treatment on neutrophils that were activated with various stimulants to produce ROS caused reduced toxic action of the ROS; for example, equol decreased the phosphorylation of the proteins regulating NADPH oxidase [91]. Phagocytic cells, after being incubated with equol for 1 h, showed a significant reduction in the intracellular production of superoxide anion and hydrogen peroxide [92].…”
Section: Antioxidative Effectmentioning
confidence: 99%